ATG5 is instrumental in the transition from autophagy to apoptosis during the degeneration of tick salivary glands. - Yanan Wang; Houshuang Zhang; Li Luo; Yongzhi Zhou; Jie Cao; Xuenan Xuan; Hiroshi Suzuki; Jinlin Zhou (Public Library of Science (PLoS), 2021)
Female tick salivary glands undergo rapid degeneration several days post engorgement. This degeneration may be caused by the increased concentration of ecdysone in the hemolymph during the fast feeding period and both autophagy and apoptosis occur. In this work, we first proved autophagy-related gene (ATG) and caspase gene expression peaks during degeneration of the tick salivary glands. We explored the regulatory role of Rhipicephalus haemaphysaloides autophagy-related 5 (RhATG5) in the degeneration of tick salivary glands. During the fast feeding phase, RhATG5 was cleaved and both calcium concentration and the transcription of Rhcalpains increased in the salivary glands. Recombinant RhATG5 was cleaved by μ-calpain only in the presence of calcium; the mutant RhATG5191-199Δ was not cleaved. Treatment with 20-hydroxyecdysone (20E) led to programmed cell death in the salivary glands of unfed ticks in vitro, RhATG8-phosphatidylethanolamine (PE) was upregulated in ticks treated with low concentration of 20E. Conversely, RhATG8-PE decreased and Rhcaspase-7 increased in ticks treated with a high concentration of 20E and transformed autophagy to apoptosis. High concentrations of 20E led to the cleavage of RhATG5. Calcium concentration and expression of Rhcalpains were also upregulated in the tick salivary glands. RNA interference (RNAi) of RhATG5 in vitro inhibited both autophagy and apoptosis of the tick salivary glands. RNAi of RhATG5 in vivo significantly inhibited the normal feeding process. These results demonstrated that high concentrations of 20E led to the cleavage of RhATG5 by increasing the concentration of calcium and stimulated the transition from autophagy to apoptosis.